2000
DOI: 10.1007/bf02439253
|View full text |Cite
|
Sign up to set email alerts
|

Activation of rat mast cells upon stimulation of protease-activated receptor (PAR-1)

Abstract: In vivo experiments on the model of wound healing showed that thrombin and thrombin receptor agonist TRAP-6 stimulated heparin secretion by mast cells in rat subcutaneous fat: the saturation of mast cells with heparin decreased, while degranulation and granulolysis increased. In vitro studies showed that TRAP-6 caused a dose-dependent release of beta-hexosaminidase from peritoneal mast cells. TRAP-6 also induced heparin release from these cells and inhibition of amidase activity of thrombin. Heparin released f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“…21 In another study thrombin did stimulate heparin and hexosaminidase release. 23 In a murine mast cell preparation thrombin stimulated IL-6 and matrix metalloproteinase 9 release and mast cell adherence to fibronectin. 24 Also, thrombin enhanced mast cell response to low-level stimulation of FceRI.…”
Section: Function Of Proteases On Cells Involved In Allergic Respiratmentioning
confidence: 99%
“…21 In another study thrombin did stimulate heparin and hexosaminidase release. 23 In a murine mast cell preparation thrombin stimulated IL-6 and matrix metalloproteinase 9 release and mast cell adherence to fibronectin. 24 Also, thrombin enhanced mast cell response to low-level stimulation of FceRI.…”
Section: Function Of Proteases On Cells Involved In Allergic Respiratmentioning
confidence: 99%
“…PARs are also expressed on cells circulating within blood, including platelets [84][85][86] and immune response cells [85,[87][88][89][90][91], expressed on glial, astrocytes and neuronal cells of the nervous system [92][93][94][95][96], as well as cells located within the corneas [97], pancreas [98], liver [99][100][101], kidney [102,103], synovium [104], skeletal muscle [105] and bone [106,107].…”
Section: Physiological and Pathophysiolo-gical Roles Of Parsmentioning
confidence: 99%
“…Both PAR-1 and PAR-2 have been identified on the MC surface [80]. In previous studies it was shown that thrombin causes degranulation of rat and human BMMCs [90,93].…”
Section: Ige−independent MC Activationmentioning
confidence: 99%